Modified combination of anti-thymocyte globulin (ATG) and post-transplant cyclophosphamide (PTCy) as compared with standard ATG protocol in haploidentical peripheral blood stem cell transplantation for acute leukemia - Barkhordar, Maryam; Kasaeian, Amir; Janbabai, Ghasem; Kamranzadeh Fumani, Hossein; Tavakoli, Sahar; Rashidi, Amir Abbas; Mousavi, Seied Asadollah; Ghavamzadeh, Ardeshir; Vaezi, Mohammad (Frontiers in Immunology, 2022)
In haploidentical peripheral blood stem cell transplantation (haplo-PBSCT), the combination of ATG and post-transplant cyclophosphamide (ATG/PTCy) has a synergistic impact in preventing graft-versus-host disease (GvHD). However, little is known about the new combination approach's long-term consequences. Our goal is to evaluate the efficacy of ATG/PTCy versus standard ATG regimen by focusing at long-term outcomes in a more homogeneous group of patients. We retrospectively included 118 adult patients up to 60 years with acute leukemia who underwent haplo-PBSCTat our single institution following the same myeloablative conditioning regimen. From 2010 to 2020, seventy-eight patients received a modified combination of ATG (2.5mg/kg/day, on days -3, -2, -1) and PTCy (40mg/kg/day on days +3, +4) compared to forty patients who had a standard ATG-based regimen (2.5mg/kg/day from days -4 to -1) from 2008 to 2015. The median follow-up time for all patients was 5.36 years, respectively. The cumulative incidence (CI) of neutrophil and platelet engraftment, as well as CMV reactivation, did not differ statistically between the two groups. The CI of acute GvHD of grades II-IV and III-IV and extensive chronic GvHD were considerably lower in the ATG/PTCy (34.6%, 8.97%, and 13.63%) than in the ATG cohort (57.5%, 30%, and 38.23%) as validated by multivariable modeling. Additionally, compared to the ATG arm, the ATG/PTCy was a hazard factor associated with a higher risk of relapse (HR=2.23, p=0.039). The probability of 5-year overall survival, disease-free survival, and GvHD-free relapse-free survival (GRFS) in the ATG/PTCy group (53.34%, 49.77%, and 36.04%) was comparable with the ATG group (47.5%, 42.5%, and 22.5%), respectively. Our finding suggested that a modified ATG/PTCy combination resulted in a lower risk of acute and chronic GvHD and a higher risk of relapse than standard ATG-based protocol but had no effect on long-term outcomes. However, certain adjustments in immunosuppression protocol are warranted to improve the outcome.